1993
DOI: 10.1016/0735-1097(93)90246-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral theophylline on sick sinus syndrome

Abstract: The results suggest that oral theophylline may be beneficial for the treatment of patients with sick sinus syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…5 Our results further indicate that A1R blockade may prevent and restore adenosine-induced atrial pauses in HF subjects. However, since A1Rs are expressed in a variety of tissues in addition to cardiac muscle, long-term use of theophylline can produce off-target side effects such as seizures 49 and therefore should be evaluated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…5 Our results further indicate that A1R blockade may prevent and restore adenosine-induced atrial pauses in HF subjects. However, since A1Rs are expressed in a variety of tissues in addition to cardiac muscle, long-term use of theophylline can produce off-target side effects such as seizures 49 and therefore should be evaluated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that oral administration of theophylline, a phosphodiesterase inhibitor, may be effective in patients with symptomatic sinus bradycardia. 5,6 Since cilostazol also has an inhibitory action on phosphodiesterase, it may be useful for treating SSS. The effects of cilostazol on intracellular cyclic adenosine monophosphate levels and cellular function have been demonstrated in cardiac ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the clinical findings that (1) bolus injection of adenosine suppresses SAN function and produces pauses especially in patients with SAN dysfunction 12, 13 and (2) orally administrated theophylline, a potent nonselective antagonist of adenosine receptors, reduces both the frequency and duration of the pauses in patients with sick sinus syndrome. 14 …”
Section: Introductionmentioning
confidence: 99%